Implementasi Pendidikan Karakter melalui Nilai-Nilai Kearifan Lokal di SD Tamansiswa Jetis Yogyakarta - Chairiyah Chairiyah (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: Implementation of Character Education Through Local Wisdom Values in SD Taman Siswa Jetis Yogyakarta. Research Grants Kopertis Region V. Sarjanawiyata Tamansiswa University. This study aims to: ( 1) Determine the implementation of character education through the values of local wisdom in SD Taman Siswa Jetis Yogyakarta, ( 2 ) determine the obstacles in the implementation of character education through the values of local wisdom in SD Taman Siswa Jetis Yogyakarta, and ( 3) to identify a solution to solve bottlenecks in the implementation of character education through the values of local wisdom in SD Taman Siswa Jetis Yogyakarta. This study used qualitative methods. To collect the data the researchers used a technique -depth interviews and direct observation techniques . Step-by- step analysis of the data using the model of Miles and Huberman , namely the presentation of data , data reduction , and confirmation, while the data validity tests include tests of internal validity , external validity , reliability, and objectivity. The results showed that the implementation of character education through the values of local wisdom in SD Taman Siswa Jetis realized in the form of learning related to local cultures, such as dance, musical, artistic painting or drawing, and learning the Java language. Besides, in the form of classroom learning, the implementation of the values of local wisdom was also done in the form of habits in school, such as 5S (smiles, greetings, greetings, manners). Barriers in implementing character education through the values of local wisdom is in addition to the factors advances in information technology that is misused by learners, family factors that less supervise the behavior of learners and communities that do not support the achievement of the goal of character education also influences, while a factor of teacher is teacher competence is lacking, especially new teachers in implementing the values of local wisdom. The solution to solve bottlenecks in the implementation of character education through the values of local wisdom is that by establishing a qualified teacher and professional manner to include teachers in professional training at local and national levels and to improve synergy between schools, families, and communities.